The application and practice of artificial intelligence in promoting the development of physical education in colleges and universities: a review - Wang, Xiuxia; Chen, Junjie; Cheng, Guangxin (Quality in Sport, 2025)
With the rapid development of artificial intelligence (AI) technology, its application in college physical education has gradually shifted from marginal exploration to system integration. Based on literature review, case study and empirical data analysis, this paper systematically explores the multi-dimensional application of AI technology in college physical education, including sports performance analysis, personalized training, teaching management optimization and intelligent evaluation. The results show that AI can effectively improve teaching efficiency, scientific training and objectivity of evaluation, while promoting the precision and fairness of physical education. Through surveys and data comparisons of multiple colleges and universities, this paper verifies the significant effectiveness of AI in improving students’ sports performance, reducing sports injury rates, and improving classroom organization efficiency. At the same time, the article also points out the challenges of current applications, such as infrastructure shortage, insufficient digital literacy of teachers, low algorithm transparency and data ethics concerns. Based on this, this paper proposes a path to promote the deep integration of AI into physical education from four dimensions: system construction, teacher empowerment, technology development and data governance. The study believes that AI will play the role of "intelligent engine" in future college physical education, promoting the transformation of the education paradigm from experience-driven to data-driven.